Depiction Heroic Animated Characters: Describing a Brief Process of Archetype Embodiment into a Genuine Nusantara -Inspired Content - Ahmad Azaini, bin manaf; Fythullah, Hamzah; Azwan, Abidin (HRMARS, 2021)
The importance of characters in in animation has received much attention in research on digital content industries, as well as an important tool for acting in animation content. This article highlighted the importance of archetypes and attributes in the Nusantara-based character design. This includes the review of current trends and envisages the weaknesses of character design in animated films, along with recommendations to improve character design’s traits, parameter, silhouette, and suggested archetype. In conclusion, well-designed animated characters of Nusantara with strong resonance imply to increased audience satisfaction. Future research is recommended to elevate a good development of character design in contributing economic benefit for 600 million population in Southeast Asia in developing Nusantara digital content.